2013
DOI: 10.1159/000348473
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a New Tonic Containing Urea, Lactate, Polidocanol, and <b><i>Glycyrrhiza inflata</i></b> Root Extract in the Treatment of a Dry, Itchy, and Subclinically Inflamed Scalp

Abstract: Background/Aims: Dry, itchy and inflamed scalp conditions are common and often associated with diseases such as atopic dermatitis or psoriasis. To improve these symptoms, we investigated the efficacy of a new tonic containing the active ingredients urea, lactate, polidocanol, and Glycyrrhiza inflata root extract, containing licochalcone A. Study Design/Methods: 30 subjects with dry and itchy scalp conditions underwent a randomized half-head study for 4 weeks, applying the leave-on tonic three times a week on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 949 publications
(34 citation statements)
references
References 123 publications
(47 reference statements)
0
33
0
1
Order By: Relevance
“…47 Schweiger et al found that scalp moisture was significantly increased, and scalp itching and tautness were significantly reduced in areas treated with the tonic compared to control. 47 Angelova…”
Section: Licorice Rootmentioning
confidence: 99%
See 4 more Smart Citations
“…47 Schweiger et al found that scalp moisture was significantly increased, and scalp itching and tautness were significantly reduced in areas treated with the tonic compared to control. 47 Angelova…”
Section: Licorice Rootmentioning
confidence: 99%
“…Schweiger et al . studied a topical tonic containing urea, lactate, polidocanol, and licorice root extract in a 4‐week, randomized, split‐scalp trial ( n = 30) in treating dry, itchy, and subclinically inflamed scalp . The tonic was applied to half of the scalp three times weekly .…”
Section: Plant Derivativesmentioning
confidence: 99%
See 3 more Smart Citations